Grammars of Identity/Alterity. A Structural Approach, Gerd Baumann y Andre Gingrich (comps.) - Díaz de Rada, Ángel (Alteridades, 2014)
Reseña del libro de Gerd Baumann y Andre Gingrich (comps.), Grammars of Identity/Alterity. A Structural Approach, Berghahn Books, Nueva York, 2004, 219 pp.